2018
DOI: 10.1038/s41374-017-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

SLC26A3 (DRA) prevents TNF-alpha-induced barrier dysfunction and dextran sulfate sodium-induced acute colitis

Abstract: SLC26A3 encodes a Cl/HCO ion transporter that is also known as downregulated in adenoma (DRA) and is involved in HCO/mucus formation. The role of DRA in the epithelial barrier has not been previously established. In this study, we investigated the in vivo and in vitro mechanisms of DRA in the colon epithelial barrier. Immunofluorescence (IF) and co-immunoprecipitation (co-IP) studies reveal that DRA binds directly to tight junction (TJ) proteins and affects the expression of TJ proteins in polarized Caco-2BBe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…We have also demonstrated that this mutation caused increased ubiquitination mediated degradation of SLC26A3, leading to decreased protein levels of SLC26A3. Our findings, along with other reports [27], demonstrated that SLC26A3 overexpression enhances intestinal epithelial cell barrier function and may explain why SNP rs386833481 mutation caused increased intestinal epithelial cell permeability. Our study is the first to supply the evidence that SLC26A3 SNP rs386833481 (c.392C>G; p.P131R) is a likely causative mutation for diarrhea and has also provided a molecular mechanism underlying this observation.…”
Section: Discussionsupporting
confidence: 88%
“…We have also demonstrated that this mutation caused increased ubiquitination mediated degradation of SLC26A3, leading to decreased protein levels of SLC26A3. Our findings, along with other reports [27], demonstrated that SLC26A3 overexpression enhances intestinal epithelial cell barrier function and may explain why SNP rs386833481 mutation caused increased intestinal epithelial cell permeability. Our study is the first to supply the evidence that SLC26A3 SNP rs386833481 (c.392C>G; p.P131R) is a likely causative mutation for diarrhea and has also provided a molecular mechanism underlying this observation.…”
Section: Discussionsupporting
confidence: 88%
“…Mutations resulting in loss of SLC26A3 expression are associated with congenital chloride diarrhea (CLD) 42 . In addition to being associated with CLD, SLC26A3 is dysregulated in intestinal inflammation 43,44 and DSS colitis severity is increased in SLC26A3 −/− mice 34,45 . Both in vivo and in vitro SLC26A3 dysregulation has been associated with decreased bicarbonate secretion and chloride absorption, but not chloride secretion 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…However, its specific role in relation to cancer development is not clear [326]. In healthy gut cells, this transporter has been found to interact with tight junction proteins and play a role in protecting the epithelial barrier, suggesting that this transporter may play a role in cellular growth or motility [312,327].…”
Section: Ph Regulation and Cancermentioning
confidence: 99%